FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSLUSIF IADA IBU MEMPUNYAI BAYI DI WILAYAH KERJA PUSKESMAS KAYU JAO KABUPATEN SOLOK - WD, Kurniati Maya Sari (Ensiklopedia Education Review, 2020)
Exclusive breastfeeding is breastfeeding only immediately after birth until the age of 6 months which is given as often as possible, unless drugs and vitamins can be given on medical indications. Based on the data obtained at the Solok District Health Office, the coverage of exclusive breastfeeding in 2016 decreased, the percentage of exclusive breastfeeding at KayuJao Health Center, Solok Regency, with a percentage of 39%. The purpose of this study was to see the factors related to exclusive breastfeeding for mothers who have babies in the Work Area of ​​the KayuJao Community Health Center, Solok Regency in 2017. This type of research is descriptive analytic. This research was conducted on 12-21 December 2017, with the sampling technique using Simple Random Sampling and obtained a total sample of 51 respondents. The data were collected and then the data was processed using a computerized system and then analyzed using univariate and bivariate analysis and then interpreted. The results showed that there was a significant relationship between experiences with exclusive breastfeeding with p-value = 0.046